Evaluation of Optimization of Pulmonary and Systemic Blood Flow in Children after Bidirectional Cavapulmonary Anastomosis - Dziuryi, Ivan V.; Truba, Iaroslav P.; Prokopovych, Liliya M.; Fylypchuk, Vasyl V.; Lazoryshynets, Vasyl V. (Ukrainian Journal of Cardiovascular Surgery, 2021)
In patients after bidirectional cavapulmonary anastomosis, blood flow through the superior vena cava (SVC), providing effective pulmonary blood flow, is the most important factor influencing blood oxygen saturation. Blood flow through the inferior vena cava recirculates into the systemic bloodstream. The study of the ratio of these flows will provide better understanding of the physiology of blood circulation after anastomosis and determine systemic oxygen saturation of blood and optimal time to perform surgery. The aim. To determine volumetric blood flow in the SVC, calculate pulmonary to systemic blood flow ratio in children after bidirectional cavapulmonary anastomosis, and evaluate its contribution to cardiac output and oxygen saturation in systemic blood flow. Materials and methods. In the period from January 2010 to June 2021, 51 patients with congenital heart defects with depleted pulmonary blood flow underwent hemodynamic correction at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. There were 29 male patients (57%) and 22 female patients (43%). The mean age of the patients at the time of the surgery was 34 ± 18.2 months (2 to 120 months), the mean age of patients at the time of examination was 43.5 ± 28.4 months (12 to 134 months). The main method of diagnosis in determining the defect and assessing the immediate and long-term results was echocardiographic examination and probing of the heart cavities. To evaluate the optimization of pulmonary/systemic blood flow we used equations obtained using the Fick method. Pulmonary to systemic blood flow ratio was calculated separately for 35 patients. Among the examined 35 patients, 18 children were older than 2.5 years, so all the examined patients were conveniently divided into 2 age groups: I group (n = 17) up to 2.5 years, II group (n = 18) older than 2.5 years to assess the contribution of SVC to the systemic circulation depending on age. Results. Pulmonary to systemic blood flow ratio was calculated for 35 patients Qp/Qs = (82% – 66%) / (97% – 66%) = 0.52. The calculated cardiac index according to echocardiography was 4.0 ± 0.85 L/min/m2 which corresponds to the SVC saturation (r = 0.60, p = <0.001). The flow in the superior vena cava = 2.08 L/min/m2. There was a very interesting trend towards decrease in the average rate of systemic saturation in patients after bidirectional cavapulmonary anastomosis depending on age and duration of surgery. Thus, in 17 patients of group I, the calculated Qp/Qs was (84% – 67%) / (97% – 67%) = 0.57. In patients of group II, the average systemic oxygen saturation was 78 ± 2% (from 65% to 81%). Calculated Qp/Qs for 18 patients of group II = (78% – 66%) / (97% – 66%) = 0.39, which indicates a decrease in pulmonary to systemic ratio with the growth of the child. Decreased systemic saturation after bidirectional cavapulmonary anastomosis in patients with increasing age and body surface area is associated with a decrease in the proportional flow from the superior vena cava. Therefore, in our clinical material, we confirmed the phenomenon of change in pulmonary to systemic ratio depending on age, which was described by Salim et al. according to a study conducted on healthy babies. Conclusions. The contribution of SVC flow to total cardiac output after bidirectional cavapulmonary anastomosis is directly associated with the patient’s age and gradually decreases in older patients, as indicated by a decrease in systemic saturation, so the clinical effect of bidirectional cavapulmonary anastomosis may be significantly better when performing surgery in early childhood.